Analisis Pemberdayaan Sosial Ekonomi di Masjid At-Taqwa - Setianto Setianto; Tika Widiastuti (Jurnal Ekonomi Syariah Teori dan Terapan, 2015)
This research aims to find out the role of At-Taqwa mosque in Simorejo Surabaya towards the community. It uses qualitative approach with descriptive case study methodology. The researcher used purposive technique for data collection to determine the informant. Based on the technique, the researcher obtained seven informants which were the head of takmir, and six mosque jamaah from At-Taqwa Simorejo Surabaya. The data collection was done bydoing observation, documentation, and in-depth interview. The analysis of the data was done by using interactive model which were data reduction, data display and drawing the conclusion.The result is At-Taqwa Simorejo mosque has a big role in social empowerment because the community is involved in productive process which is based on equality and security, sustainability and cooperation which can run simultaneously so that prosperity can be achieved.